2020
DOI: 10.3390/su12187275
|View full text |Cite
|
Sign up to set email alerts
|

Measuring What Is Not Seen—Transparency and Good Governance Nonprofit Indicators to Overcome the Limitations of Accounting Models

Abstract: One of the most complex challenges currently faced by non-profit organizations (NPOs) is demonstrating that they manage resources with the highest levels of efficiency and excellence, and do not deviate from the accomplishment of their mission. Transparency and good governance are highly valuable issues for the survival of these organizations. However, empirical studies and models to measure these concepts are scarce and lack consensus. The objective of this article is to develop a uniform procedure for measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
0
13
0
4
Order By: Relevance
“…Moreover, researchers suggested that perceived transparency leads to increased public trust in government (Mansoor, 2021a;Moreno-Albarracı ´n et al, 2020). While overall public trust is based on fairness and expectation from the authorities that make decisions to safeguard people's welfare (Houston and Harding, 2013) and technology can aid in making this information accessible to the public.…”
Section: The Mediating Role Of Perceived Effectiveness Of E-governancementioning
confidence: 99%
“…Moreover, researchers suggested that perceived transparency leads to increased public trust in government (Mansoor, 2021a;Moreno-Albarracı ´n et al, 2020). While overall public trust is based on fairness and expectation from the authorities that make decisions to safeguard people's welfare (Houston and Harding, 2013) and technology can aid in making this information accessible to the public.…”
Section: The Mediating Role Of Perceived Effectiveness Of E-governancementioning
confidence: 99%
“…In this study we show that the formalization of a process for indicators weighting may contribute to literature by improving the measurement of transparency in the Non-profit Sector. In line with recent studies that propose the use of multi-criteria decision-making optimization techniques (see, for example Moreno-Albarracín et al, 2020), but focusing specifically on transparency, we aim to improve NPO accountability by, empirically validating proposals made by public authorities. Our results show that the block of indicators that are considered to be the most important when measuring transparency in NPOs are those from TR4 block "Structure and composition of their budgeting process and activities, and their economic and financial structure" (consensus value = 0.517), and those from TR2 block "Definition of the mission, vision, and values" (consensus value = 0.252).…”
Section: Conclusion and Limitationsmentioning
confidence: 96%
“…However, a few problems arise. The indicators proposed by those entities are not homogeneous, they are not included in all of the set and their different weights differ depending on which institution proposes them (Moreno-Albarracín et al, 2020).…”
Section: Transparency Of Npos In Spainmentioning
confidence: 99%
“…Transparency refers to the obligation or initiative of a charity to disclose key information about the organization, such as financial reporting, management practices, and effectiveness. To improve the governance of CFs and alleviate information asymmetries, there are mandatory and voluntary information disclosures to improve the transparency of CFs [6]. As for mandatory disclosures, government regulations require disclosures and related information to be provided to users of the charity [5].…”
Section: Asymmetric Information and The Transparency Of Cfsmentioning
confidence: 99%
“…Due to wide social supporting roles and participation, COs are playing an increasingly important and active role during the decision-making and the implementation process for social sustainability, in both the public and private sectors, as well as at both the national and international level [4,5]. The contributions of COs, together with other nonprofit organizations, to sustainable social developments have been well recognized and acknowledged by both the academic community and international organizations [2,4,6].…”
Section: Introductionmentioning
confidence: 99%